Experimental investigation on rheological properties of cemented silica fume paste for application of geotechnical engineering - Lim, Kwang Seng (Universiti Malaysia Sarawak, (UNIMAS), 2020)
The main study of this research is to determine the rheological properties of cemented silica fume paste when varies percentage of cement content replaced the silica fume using the rotational viscometer (HAAKE Viscotester 7 plus). Silica fume is an industrial waste produce in the electric arc furnace (EAF). Due to its increasing volume, many researchers have tried to explore the use of silica fume. From the previous research, it shows that silica fume can be used as a mineral admixture to replace the amount of cement on the fresh and hardened concrete in order to improve concrete durability. Silica fume is also used in other application such as geotechnical engineering. However, there are no research has been published in the past regarding the effect of cement content on the rheological properties of cemented silica fume paste with the major materials of silica fume since most of the research is concerned with the use of silica fume in concrete industry with the major materials of cement content in the cemented silica fume paste. Therefore, a new research needs to be done in order to utilize rheological measurements in cemented silica fume paste using different dosage of cement as an indicator to evaluate the suitability of silica fume for the geotechnical engineering purpose. In this research, the specimens of the cemented silica fume paste were proceeded with the rheological properties test and the unconfined compressive strength (UCS) test to determine the shear stress, viscosity and the shear strength. The properties of the dry silica fume were initially determined by conducting laboratory tests such as grain size distribution, liquid limit, plastic limit, moisture content (natural state) and specific gravity. In the same way, scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) also be conducted to see the surface phenomena and undergo the chemical analysis. In this study, the proportion of cement are varying from 0 to 30% in steps of 5% with the varies of water/solid (W/B) ratio from 0.8 to 1.0. There is not any reference for deciding the proportion of cement content and W/B ratio since no work has been reported in the past. The result of the rheological properties test show that most of the mix of cemented silica fume paste show the plastic behaviour (Herschel and Bulkley) flow based on the log shear stress against the log shear rate curve drawn. The result of W/B ratio of 0.9 show that 15% of replacement is the optimum replacement whereas the result of W/B ratio of 0.8 and 1.0 show inconsistent result which is same as the result of shear stress obtained for the UCS test. Therefore, further research on the rheological properties of cemented silica fume 11 paste in geotechnical engineering should be carried out to provide better compatibility of the laboratory findings for future references as there is lack of application of silica fume in rheological properties for the application of geotechnical engineering.